ESPIRITUALIDADE NAS ORGANIZAÇÕES: Um Estudo de Caso de sua influência na Cultura Organizacional - CALDAS, JALMAR RIBEIRO (2018)
From the 1990s, with the advent of the "New Economy" and the process of globalization, organizations begin to undergo cycles of structural change as a result of increasingly frequent socioeconomic changes. As a consequence, the only rule becomes uncertainty. In view of this set of factors of transformation of the present times, it is that organizations and the human being begin to feel the need for a larger dimension, which encompasses, integrates and completes them in a holistic and symbiotic way. A new dimension emerges as a way of complementing and responding to their doubts and needs: spirituality. Spirituality becomes the "amalgam", the differentiation for a competitive and profitable organization and the link with its collaborators. In addition, it becomes the factor that guides the interaction between the individual, the work environment and society, generating more salutary, productive, and, above all, more ethical and human dynamics. It is from this new perspective and necessity of the human and corporate spheres that the theme organizational spirituality assumes growing importance and more prominent in the scientific and corporate media of the XXI century. Spirituality thus comes to occupy a gap created in the process of globalization: the economy is globalized, but not the social, the human, and consequently the organizational cultures. It is within this complex context that this research tries to evaluate how spirituality influences culture and organizational values, as perceived by managers and collaborators, what their results are and how this is sustained, or not, over time. In this sense, the general objective of this research is to understand the influences of the dimensions of spirituality in the context of the corporate culture of a private organization and how this dynamic occurs. For this purpose, a qualitative exploratory research was developed, using the case study method in a private multinational organization in São Paulo. Thus, through the triangulation of data, it was possible to verify that the entity researched is an organization that has in its organizational culture values of spirituality that are practiced, documented and perceived by its employees in the reality of the organization. There was a daily dynamic of work that led the organization to an intense sharing of knowledge and the creation of an environment extremely favorable to innovation. The organization's managers demonstrated in their reports that they are dedicated to the development of highly ethical, righteous and collaborative practices, developing an environment in which transparency, trust and sense of purpose are present factors among its members, phenomena confirmed by the perception of its employees. We could also verify that the organization originated and has its development and perpetuity using these dimensions in a strong organizational culture preserved in its organizational values in an immutable way, through practices emphasized until the present day. These long-term results can characterize a phenomenon and an example to other organizations for the creation and maintenance of a pleasant, dynamic and collaborative environment, or that generates new knowledge to become a barn of new ideas and innovation. In this context, and through the results, we have responded to the research question, which is "How do dimensions of spirituality influence organizational culture?" This study opens space for new and future research in different organizations in order to contribute with new information and more comprehensive conclusions.